On the use of low and high cycle fatigue damage models - Abdel Wahab, Magd; Hilmy, Irfan; Hojjati-Talemi, Reza (Trans Tech Publications, Switzerland, 2013)
In this paper, Continuum Damage Mechanics (CDM) theory is applied to low cycle and high cycle fatigue problems. Damage evolution laws are derived from thermodynamic principles and fatigue number of cycles to crack initiation is expressed in terms of the range of applied stresses, triaxiality function and material constants termed as damage parameters as function of stress are extracted from fatigue test and the damage model. High cycle fatigue damage model is applied to fretting fatigue test specimens and is integrated within a Finite Element Analysis (FEA) code in order to predict the number of cycles to crack initiation. Fretting fatigue problems involve two types of analyses: namely contact mechanics and damage /fracture mechanics. The high cycle fatigue damage evolution law takes into account the effect of different parameters such as contact geometry, axial stress, normal load and tangential load.